2023
DOI: 10.1002/cbin.12065
|View full text |Cite
|
Sign up to set email alerts
|

The role of peroxisome proliferator‐activated receptor γ in lipid metabolism and inflammation in atherosclerosis

Abstract: Cardiovascular disease events are the result of functional and structural abnormalities in the arteries and heart. Atherosclerosis is the main cause and pathological basis of cardiovascular diseases. Atherosclerosis is a multifactorial disease associated with dyslipidemia, inflammation, and oxidative stress, among which dyslipidemia and chronic inflammation occur in all processes. Under the influence of lipoproteins, the arterial intima causes inflammation, necrosis, fibrosis, and calcification, leading to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 178 publications
0
4
0
Order By: Relevance
“…In addition, VCE-004.8 is a dual agonist of PPARγ and CB2R 14 . PPARg and CB2R are preclinically validated therapeutic targets for vascular inflammation and atherosclerosis 45,46,47 . For instance, foam cells play a vital role in the initiation and development of atherosclerosis since they are the major sources of necrotic core in atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VCE-004.8 is a dual agonist of PPARγ and CB2R 14 . PPARg and CB2R are preclinically validated therapeutic targets for vascular inflammation and atherosclerosis 45,46,47 . For instance, foam cells play a vital role in the initiation and development of atherosclerosis since they are the major sources of necrotic core in atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…PPARG is involved in multitarget and multipathway anti-AS actions such as inflammatory response, myocardial vascular smooth muscle value-added, and vascular endothelial function. The expression of TNF-α, IL-1β, and IL-6 in rat aorta was significantly increased after intervention with PPARG inhibitor in a high-fat-diet-induced rat model, indicating that PPARG has a clear anti-inflammatory effect [ [41] , [42] , [43] ]. SRC is involved in the progression of AS by promoting cell proliferation, migration, and lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, although we have provided no evidence that the key lipolytic genes are direct downstream transcriptional targets of NFE2L1, RNA profiles of BAC/BAT of current study along with previous findings on the mRNA expression of lipolytic genes in WAC/WAT [ 11 , [18] , [19] , [20] , [21] ] highly suggest that NFE2L1 is one of the key factors that control the transcription of the lipolytic genes. In addition, emerging evidence indicates that multiple factors, PPARγ in particular, are involved in the transcriptional activation or repression of the key lipolytic genes [ 40 , 41 ]. Interestingly, our previous mechanistic studies in 3T3-L1 cells indicated that NFE2L1 regulates the expression of Pparγ2 in an isoform-specific manner [ 21 ].…”
Section: Discussionmentioning
confidence: 99%